Occupational Health Profile of Neurointerventionists in Indonesia: A National Cross-Sectional Survey Study - Fritz Sumantri Usman; Merlin Prisillia Kastilong; Leny Kurnia; Hugo Dwiputra Wiradarma; Petrus Nilwan Ginting; Bambang Sutrisno; Evlyne Erlyana Suryawijaya (Neurointervention Working Group of Indonesian Neurological Association, 2026)
Highlight: First national survey of neurointerventionists in Indonesia Fatigue, sleep disturbance, and musculoskeletal pain were common Radiation monitoring and occupational protection remin limited ABSTRACT Introduction: Neurointerventional practice may increase the risk for musculoskeletal problems, fatigue, and sleep disturbance due to prolonged radiation exposure, physical strain, and irregular working hours. However, data from developing countries remains limited. Objective: This study aimed to provide information and analyze the occupational health profile and associated risk factors among neurointerventionists in Indonesia. Method: A national cross-sectional survey was conducted using a structured questionnaire assessing demographic profiles, workload, radiation protection practices, and health outcomes. Associations between variables were analyzed using appropriate statistical tests. Result: A total of 150 neurointerventionists participated in this study. Most were male (76%) and aged 40-49 years (48%). Nearly half performed <2 procedures weekly (48.7%), while 67.3% spent <5 hours in the catheterization laboratory. Although protective equipment use was common, only 34.7% consistently wore dosimeters, and 19.3% routinely monitored radiation exposure. Musculoskeletal pain was reported by 35.3% of participants, while fatigue and sleep disturbance affected 68.7% and 32.7% of participants, respectively. Musculoskeletal pain was significantly associated with fatigue, sleep disturbance, shorter sleep duration, and higher on-call workload, whereas regular exercise showed a protective effect (all p < 0.05). Longer catheterization laboratory duration was also associated with fatigue and sleep disturbance (p = 0.033 and p = 0.048, respectively). Conclusion: Neurointerventionists in Indonesia face significant occupational health challenges. Targeted strategies, such as workload management, improved radiation monitoring, and institutional support, are required.